Efeito da vitamina D sobre o equilíbrio postural em mulheres na pós-menopausa - Oliveira, Luciana Mendes Cangussu [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objective: to evaluate the effect of isolated vitamin D (VitD) supplementation on the rate of falls and the postural balance in fallers postmenopausal women. Methods: In this double-blind placebo controlled trial 160 women with age 50-65 years, amenorrhea ≥ 12 months and history of falls were included. Participants were allocated at random to receive either 1,000UI VitD /day orally (n = 80) or placebo (n = 80). The intervention time was 9 months, with assessments at initial and final moments. Postural balance was assessed by stabilometry (computerized force platform). Muscle mass was estimated by Total-body DEXA and muscle strength by handgrip strength and chair-rising test. Serum levels of 25-hydroxyvitamin D [25(OH)D] were measured by HPLC. Data were analyzed according to intention-to-treat, using ANOVA, chi-square and logistic regression. Results: After 9 months, mean 25(OH)D levels increased from 15.0±7.5 ng/ml to 27.5±10.4 ng/ml (+45.4%) in the VitD group whereas decreased from 16.9±6.7 ng/ml to 13.8±6.0 ng/ml (-18.5%) in the placebo group (p<.001). The rate of fall was higher in the placebo (+46.3%, p<.001), that presented an adjusted risk of 1.9 (CI 95% 1.23-3.08) times higher of falls and 2.80 (CI 95% 1.43-5.50) times higher of recurrent falls than the VitD group. There was reduction in body sway by stabilometry, with lower amplitude of anteroposterior (-35.5%) and laterolateral (-37.0%) oscillation, only in the VitD group (p<.001). In this group, there was significant increased in muscle strength of the lower limbs by chair-rising test (+45.5%, p=0.036). Women in the placebo group presented significant reduction in the muscle mass (-5.8%) (p=0.030). Conclusion: Fallers postmenopausal women with isolated vitamin D supplementation had a lower rate of falls and improvement in postural balance and muscle strength

Objetivo: Avaliar o efeito da suplementação isolada de vitamina D (VD) sobre a ocorrência de quedas e o equilíbrio postural em mulheres na pós-menopausa com histórico de quedas. Métodos: Foi conduzido ensaio clínico, duplo-cego, placebo-controlado envolvendo 160 mulheres, idade 50-65anos, amenorréia ≥12 meses, com histórico de quedas. As participantes foram randomizadas em dois grupos: VD 1000UI/dia via oral (n=80) ou placebo (n=80). O tempo de intervenção foi nove meses, com avaliações nos momentos, inicial e final. Foram avaliados: o equilíbrio pela estabilometria (plataforma de força computadorizada), a massa muscular pela densitometria de corpo total, e a força muscular pelo teste de pressão manual e teste do agachamento. Os valores séricos de 25(OH)D foram mensurados por HPLC. A análise estatística foi por intenção de tratamento (ITT), empregando-se ANOVA, Qui-Quadrado e Regressão Logística. Resultados: Após nove meses, valores médios de 25(OH)D aumentaram de 15,0±7,5 ng/ml para 27,5±10,4 ng/ml (+45.4%) no grupo VD, e diminuíram de 16,9±6,7 ng/ml para 13,8±6,0 ng/ml (-18.5%) no placebo (p<0.001). A ocorrência de quedas foi maior no grupo placebo (+46.3%) com risco ajustado de 1,95 (IC 95% 1,23-3,08) vezes maior de quedas e 2,80 (IC95% 1,43-5,50) vezes maior de quedas recorrentes quando comparado ao grupo VD (p<0.001). Observou-se redução da oscilação corporal pela estabilometria, com menor amplitude ântero-posterior (-35.5%) e latero-lateral (-37.0%) (p<0.001); e aumento da força muscular (+45.5%) pelo teste do agachamento (p=0.036) apenas no grupo VD. Nas mulheres do grupo placebo houve redução (-5.8%) na massa muscular (p=0.030). Conclusão: Em mulheres na pós-menopausa com histórico de quedas, a suplementação isolada de vitamina D repercutiu em menor ocorrência de quedas e melhora no equilíbrio postural e na força muscular
Keywords: Mulheres; Distúrbios da postura; Vitamina D; Pós-menopausa; Quedas (Acidentes); Postmenopause; Vitamin D